The Genealogical Divergence Index Across a Speciation Continuum in Hercules Beetles. Issue 6 (16th November 2021) - Huang, Jen-Pan
Abstract: The genealogical divergence index ( gdi ) was developed to aid in molecular species delimitation under the multispecies coalescent model, which has been shown to delimit genetic structures but not necessarily species. Although previous studies have used meta-analyses to show that gdi could be informative for distinguishing taxonomically good species, the biological and evolutionary implications of divergences showing different gdi values have yet to be studied. I showed that an increase in gdi value was correlated with later stages of divergence further along a speciation continuum in an Amazonian Hercules beetle system. Specifically, a gdi value of 0.7 or higher was associated with diverge between biological species that can coexist in geographic proximity while maintaining their evolutionary independence. Divergences between allopatric species that were conventionally given subspecific status, such as geographic taxa that may or may not be morphologically divergent, had gdi values that fell within the species delimitation ambiguous zone (0.2 < gdi < 0.7). However, the results could be drastically affected by the sampling design, i.e., the choice of different geographic populations and the lumping of distinct genetic groups when running the analyses. Different gdi values may prove to be biologically and evolutionarily informative should additional speciation continua from different empirical systems be investigated, and the results obtained may help with objectively delimiting species in the era of integrative taxonomy.